Listeners with congenital amusia are sensitive to context uncertainty in melodic sequences. (30th July 2021) - Quiroga-Martinez, D.R.; Tillmann, B.; Brattico, E.; Cholvy, F.; Fornoni, L.; Vuust, P.; Caclin, A.
Abstract: In typical listeners, the perceptual salience of a surprising auditory event depends on the uncertainty of its context. For example, in melodies, pitch deviants are more easily detected and generate larger neural responses when the context is highly predictable than when it is less so. However, it is not known whether amusic listeners with abnormal pitch processing are sensitive to the degree of uncertainty of pitch sequences and, if so, whether they are to a different extent than typical non-musician listeners. To answer this question, we manipulated the uncertainty of short melodies while participants with and without congenital amusia underwent EEG recordings in a passive listening task. Uncertainty was manipulated by presenting melodies with different levels of complexity and familiarity, under the assumption that simpler and more familiar patterns would enhance pitch predictability. We recorded mismatch negativity (MMN) responses to pitch, intensity, timbre, location, and rhythm deviants as a measure of auditory surprise. In both participant groups, we observed reduced MMN amplitudes and longer peak latencies for all sound features with increasing levels of complexity, and putative familiarity effects only for intensity deviants. No significant group-by-complexity or group-by-familiarity interactions were detected. However, in contrast to previous studies, pitch MMN responses in amusics were disrupted in high complexity and unfamiliar melodies. The present results thus indicate that amusics are sensitive to the uncertainty of melodic sequences and that preattentive auditory change detection is greatly spared in this population across sound features and levels of predictability. However, our findings also hint at pitch-specific impairments in this population when uncertainty is high, thus suggesting that pitch processing under high uncertainty conditions requires an intact frontotemporal loop. Highlights: Neural mismatch responses to deviant sounds are smaller in melodic contexts with increasing pitch complexity. The familiarity of melodies modulates responses to sound-intensity deviants. Listeners with amusia, a condition disrupting pitch processing, are sensitive to the pitch complexity of the melodies. Neural responses to pitch deviants are disrupted in amusics for high-complexity and unfamiliar melodies.